NONLINEAR ANALYSIS OF THE BEHAVIOR & PERFORMANCE OF MULTISTORY STEEL BUILDING STRUCTURES WITHOUT AND WITH STEEL PLATE SHEAR WALLS - P Adi Yasa; I Gede Adi Guna Apriana; Ida Bagus Prastha Bhisama; Made Hendra Prayoga (Jurnal Ilmiah Teknik Sipil, 2025)
Indonesia, as a region highly susceptible to earthquakes, necessitates the construction of earthquake-resistant buildings, particularly multi-story steel structures. Steel Plate Shear Walls (SPSWs) offer an effective solution for resisting lateral loads. This research compares the behavior and performance of three (3) building models: an Open Frame (OF) Model, a Uniform Thickness Steel Plate Shear Wall (SPSW-UT) Model, and a Varied Thicknesses Steel Plate Shear Wall (SPSW-VT) Model. Linear analysis are running with equivalent static to get the structural behaviour & pushover for nonlinear analysis to get the structural performance. In terms of structural behavior, the inclusion of SPSWs in both the SPSW-UT and SPSW-VT models significantly enhances structural stiffness, evidenced by a drastic reduction in the fundamental period compared to the OF Model (without SPSW). The SPSW-UT Model reduces inter-story drift by up to 34.23% (X-direction) and 50.69% (Y-direction), while the SPSW-VT Model also shows similar reductions of up to 30.98% (X-direction) and 49.80% (Y-direction) compared to the OF Model. From a performance point view’s, the SPSW-UT Model increases the maximum base shear by up to 20.19% (X-direction) and 32.29% (Y-direction), while the SPSW-VT Model increases it by up to 13.34% (X-direction) and 25.96% (Y-direction) compared to the OF Model. Furthermore, both SPSW models achieve an Immediate Occupancy (IO) performance level for both pushover directions, whereas the OF Model only reaches IO in the X-direction and Damage Control (DC) in the Y-direction, demonstrating a significant performance improvement due to the use of steel plate shear walls.